Surgical treatment of oral leukoplakia - Kolenko, Yuliia (Journal of Education, Health and Sport, 2017)
Background: The effectiveness of care for patients with leukoplakia depends on how timely and accurately the disease was diagnosed and also by the subsequent choice of the optimal method of treatment. In recent decades, surgery is increasingly using methods that are alternative to standard surgical methods. Purpose: to justify, develop and evaluate treatment algorithm of verrucous and erosive-ulcerative forms of oral leukoplakia with a SIN2 histological structure. Materials and Methods: to achieve this goal, a comprehensive clinical and laboratory examination of 155 patients with oral leukoplakia was performed, which appealed to the Department of Therapeutic Dentistry of the Bogomolets National Medical University in the period from 2011 to 2015. All patients underwent clinical and laboratory tests. Results: after removal of the affected area of the mucosa by radiation of an erbium laser, wound healing under fibrinous plaque was observed at 7.0 ± 0.5 days. When excision of the mucous membrane with a scalpel, the healing took place under the iodinine swab through the granulation phase for 14.0 ± 1.5 days. In patients after the operation of excision of the area of verrucous or erosive-ulcerative oral mucosa leukoplakia with laser radiation without antimicrobial and anti-inflammatory therapy on the third day, in 95% of cases there is no pain syndrome and collateral edema in the postoperative area. After traditional treatment, despite the use of antibiotics and non-steroidal anti-inflammatory drugs, 56% of patients complained of pain, and 62% had collateral edema. Conclusions: the use of ErrYAG laser laser radiation in the surgical treatment of patients with verrucous and erosive-ulcerative forms of leukoplakia promotes acceleration of healing processes of a postoperative wound twice as fast as in the control group. The use of laser technology reduces the risk of inflammatory purulent complications and helps to prevent the recurrence of the disease.